ZOO PLANKTON FAUNA AND ABIOTIC FACTORS OF WATER ENVIRONMENT IN GROWING PONDS - Приліпко, Т. М.; Якубаш, Р. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The results of studies on the natural fodder growing ponds. Established that dominant during the season was Bosminalongirostris OF Muller with an average number of 13,2 thousand. Ind/m3, biomass 0,128 g/m3. In growing pond zooplankton maximum number of Copepoda crustaceans found in June and July, the number of, respectively, 22,8 and 25,2 thousand. Ind / m3 and biomass 0,5 and 0,3 g/m3. Development cladocera crustaceans celebrated in June, July and August. During the growing season tsoholitok cultivation of carp in the growing pond pH value (pH) of water was slightly alkaline reaction ranged from 7,45 to 7,80. The water in the ponds is mineral medium amount of ions varied during the growing season growing fish from 213,6 to 272,5 mg/dL. In ionic composition is dominated by ions NSO3- (53,46-64,44 eq.%) And calcium ions (8,15-13,48 eq.%). The maximum concentration of Cl- ions in water ponds does not exceed 7,4 mg/l and the minimum – 5,7 mg/l. SO4 2- concentration ranges 32,0-40,0 mg/l. The nature of ion composition growing water ponds belong to the hydrocarbon composition of calcium. In the study of hydrochemical regime was found that all parameters were within normal limits throughout the study period. During the growing season the number of zooplankton in the growing pond ranged from 14,8 to 474,0 thousand. Ind/m3, and biomass - from 0,161 to 2,704 g/m3.Vyroschuvalni ponds on the holding in its climatic conditions are the fourth breeding area (106-120 days with temperatures over 15°C).